Diagnostic difficulties in peripancreatic tuberculous lymphadenitis: A case report - Enver İLHAN and Nazif ERKAN and Mehmet YILDIRIM and Alper F. POLAT and Kadri ÇIRAK and Arsenal SEZGİN (Turkish Journal of Gastroenterology, 2019)
-